2019
DOI: 10.31871/ijntr.5.10.16
|View full text |Cite
|
Sign up to set email alerts
|

The Antibacterial Activity Screening of the Extracts of Some Moroccan Medicinal Plants

Abstract: The antibacterial and antifungal activities of some Moroccan medicinal plants extracts were evaluated against six bacterial species and three yeasts. The agar diffusion method was used to evaluate the antimicrobial activity of the extracts of the following medicinal plants: Rosmarinus officinalis, Salvia officinalis, Psidium guajava, Crocus sativus, Dysphania ambrosioides, Trigonella foenum graecum and Cymbopogon citratus. The used standard antibiotic is the Ampicillin 30µg, and the standard antifungal is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Celiktas et al (2007) reported in their study that methanol extracts of rosemary showed low activity against S. aureus but ineffective against other microorganisms. However, in another study, rosemary extracted in ethanol and dichloromethane had a high antimicrobial effect against E. coli and Pseudomonas sp., with inhibition zone diameters ranging from 16.6 -26 mm (Lahlou et al, 2019). The antibacterial effect of rosemary is suggested to be due to its compounds such as flavonoids and phenolics (Lahlou et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Celiktas et al (2007) reported in their study that methanol extracts of rosemary showed low activity against S. aureus but ineffective against other microorganisms. However, in another study, rosemary extracted in ethanol and dichloromethane had a high antimicrobial effect against E. coli and Pseudomonas sp., with inhibition zone diameters ranging from 16.6 -26 mm (Lahlou et al, 2019). The antibacterial effect of rosemary is suggested to be due to its compounds such as flavonoids and phenolics (Lahlou et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Phytochemicals exist in several major groups such as phenols, flavonoids, carotenoids, terpenoids, alkaloids, saponins, and tannins with distinct chemical structures (Adebo and Gabriela Medina-Meza, 2020;Loi et al, 2020). These plant chemicals exhibit diverse attributes such as antimicrobial, anti-inflammatory, antioxidant, anticarcinogenic, anthelmintic, antiproliferative, and antigenotoxic effects, providing therapeutic efficacy against ailments or pathogens (Makhafola et al, 2017;Lahlou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%